2011
DOI: 10.1115/1.4004993
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Model of Passive Muscle Viscosity

Abstract: The material properties of passive skeletal muscle are critical to proper function and are frequently a target for therapeutic and interventional strategies. Investigations into the passive viscoelasticity of muscle have primarily focused on characterizing the elastic behavior, largely neglecting the viscous component. However, viscosity is a sizeable contributor to muscle stress and extensibility during passive stretch and thus there is a need for characterization of the viscous as well as the elastic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 42 publications
2
60
2
Order By: Relevance
“…However, due to the lack of the viscoelastic mechanical characterization, our main objective is not the study of the dynamic mechanical response to a load with a high displacement rate, but rather the static mechanical response to a high IAP. The characterization of viscoelastic properties of muscle would be useful to define more realistic material properties and would allow the simulation of dynamic processes [38]. This experimentation is within the scope of future works.…”
Section: Limitationsmentioning
confidence: 99%
“…However, due to the lack of the viscoelastic mechanical characterization, our main objective is not the study of the dynamic mechanical response to a load with a high displacement rate, but rather the static mechanical response to a high IAP. The characterization of viscoelastic properties of muscle would be useful to define more realistic material properties and would allow the simulation of dynamic processes [38]. This experimentation is within the scope of future works.…”
Section: Limitationsmentioning
confidence: 99%
“…Samples underwent five cycles of load-relaxation in increments of approximately 3% strain and 300-second relaxation periods. Operating in this range ensured that tissue would not be strained to the point of creating damage or plastic deformation (Meyer et al 2011). Force measurements were sampled at 20 Hz using a 1000-gf load cell (Transducer Techniques, Temecula, CA), and the second Piola-Kirchoff stress was calculated as the force divided by the initial cross-sectional area.…”
Section: Methodsmentioning
confidence: 99%
“…This requires different values of the material parameters {a, b} to define during loading and unloading, see Eq. (25). The graph on the right shows a change in slope at t = 5 s indicating the change in loading rate at λ = λ r .…”
Section: Stress Relaxationmentioning
confidence: 99%
“…It can be shown that by expressing B d in its spectral form that the expression A d · I is nonnegative so that (49) is satisfied by the functional form (25) for .…”
Section: Robust Strongly Objective Numerical Integration Algorithmmentioning
confidence: 99%
See 1 more Smart Citation